Professional competences of controllers: The case of Poland - Bohumi Král; Grzegorz Mikołajewicz; Jarosław Nowicki; Libuše Šoljaková (European Financial and Accounting Journal, 2017)
The article presents the results of the project regarding the development of the requirements to controllers' professional competences. The aim of the empirical part of the study is to assess the current situation in Poland in this field. During the study, opinions of two expert groups are compared. The respondents from the first group are responsible for development of controllers' professional competences and education. The respondents from the second group act as controllers in everyday business. The research refers to the following areas of controllers' work: their position in the company, general and specific content of controllers' activities, their authority and responsibility, requirements for education, requirements for ICT competencies, professional skills and practical experience, their role in ethical aspects of business, selection of potential candidates for a controller position, requirements to their continuing professional development and quality assurance of controllers' work as well as the importance of analysed areas for an effective controlling system in enterprise.
Keywords: M41; 650; Controller; Education; Experience; Professional Competence; Quality assurance; Skills